Low Testosterone, but Not Estradiol, Is Associated With Incident Falls in Older Men: The International MrOS Study. (27th February 2017) - Vandenput, Liesbeth; Mellström, Dan; Laughlin, Gail A; Cawthon, Peggy M; Cauley, Jane A; Hoffman, Andrew R; Karlsson, Magnus K; Rosengren, Björn E; Ljunggren, Östen; Nethander, Maria; Eriksson, Anna L; Lorentzon, Mattias; et al.
ABSTRACT: Fracture risk is determined by bone strength and the risk of falls. The relationship between serum sex steroids and bone strength parameters in men is well known, whereas the predictive value of sex steroids for falls is less studied. The aim of this study was to assess the associations between serum testosterone (T) and estradiol (E2) and the likelihood of falls. Older men (aged ≥65 years) from the United States ( n  = 1919), Sweden ( n  = 2495), and Hong Kong ( n  = 1469) participating in the Osteoporotic Fractures in Men Study had baseline T and E2 analyzed by mass spectrometry. Bioavailable (Bio) levels were calculated using mass action equations. Incident falls were ascertained every 4 months during a mean follow‐up of 5.7 years. Associations between sex steroids and falls were estimated by generalized estimating equations. Fall rate was highest in the US and lowest in Hong Kong (US 0.50, Sweden 0.31, Hong Kong 0.12 fall reports/person/year). In the combined cohort of 5883 men, total T (odds ratio [OR] per SD increase = 0.88, 95% confidence interval [CI] 0.86–0.91) and BioT (OR = 0.86, 95% CI 0.83–0.88) were associated with incident falls in models adjusted for age and prevalent falls. These associations were only slightly attenuated after simultaneous adjustment for physical performance variables (total T: OR = 0.94, 95% CI 0.91–0.96; BioT: OR = 0.91, 95% CI 0.89–0.94). E2, BioE2, and sex hormone‐binding globulin (SHBG) were not significantly associated with falls. Analyses in the individual cohorts showed that both total T and BioT were associated with falls in MrOS US and Sweden. No association was found in MrOS Hong Kong, and this may be attributable to environmental factors rather than ethnic differences because total T and BioT predicted falls in MrOS US Asians. In conclusion, low total T and BioT levels, but not E2 or SHBG, are associated with increased falls in older men. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.